Creativity and cultural improvisation - Hallam, Elizabeth; Ingold, Tim (Oxford Berg, 2007)
There is no prepared script for social and cultural life. People work it out as they go along. Creativity and Cultural Improvisation casts fresh, anthropological eyes on the cultural sites of creativity that form part of our social matrix. The book explores the ways creative agency is attributed in the graphic and performing arts and in intellectual property law. It shows how the sources of creativity are embedded in social, political and religious institutions, examines the relation between creativity and the perception and passage of time, and reviews the creativity and improvisational quality of anthropological scholarship itself. Individual essays examine how the concept of creativity has changed in the history of modern social theory, and question its applicability as a term of cross-cultural analysis. The contributors highlight the collaborative and political dimensions of creativity and thus challenge the idea that creativity arises only from individual talent and expression.